Cyclostrophic Corrections of AVISO/DUACS Surface Velocities and Its Application to Mesoscale Eddies in the Mediterranean Sea. Issue 12 (12th December 2019) - Ioannou, Artemis; Stegner, Alexandre; Tuel, Alexandre; LeVu, Briac; Dumas, Franck; Speich, Sabrina
Abstract: Mesoscale eddies, having a characteristic radius equal or larger than the local deformation radius, are generally considered to be geostrophic. Even if this is true for most of them, there are few cases where the ageostrophic velocity components induced by the local curvature of the streamlines are not negligible. In order to account for this ageostrophic part, we investigate the performance of an optimized iterative method which computes the cyclostrophic corrections starting from the geostrophic surface velocity of the AVISO (Archiving, Validation and Interpretation of Satellite Oceanographic data)/DUACS (Data Unification and Altimeter Combination System). We optimized the convergence of the iterative method using an intermediate cubic interpolation. The performance and the accuracy of the optimized iterative method is first evaluated on idealized eddies for which we can obtain their exact cyclogeostrophic solution. Mesoscale eddies of various shapes, intensities and different ellipticity are investigated. The iterative method is then applied to 15 years (2000–2015) of AVISO/DUACS geostrophic velocity fields, gridded at 1/8 o for the Mediterranean Sea. We found that these ageostrophic corrections are needed for most of the mesoscale anticyclones that have a geostrophic vortex Rossby number larger than R o >0.1. Both the Alboran and the Ierapetra eddies are frequently affected by the cyclostrophic corrections that may exceed 50 cm s −1 . Lastly, the corrected velocity fields are compared with available in situ observations of velocity measurements (vessel‐mounted acoustic Doppler current profilers) performed within the Ierapetra eddy confirming the benefit of the proposed method. Key Points: The performance of an optimized iterative method for recovering cyclogeostrophic balance is evaluated on mesoscale eddies Strong cyclostrophic corrections are required for intense anticyclones in the Mediterranean Sea Cyclogeostrophic velocity fields are in better agreement with in‐situ measurements